DISSOLUTION IN MOLTEN SILICATES: EFFECTS OF SOLID SOLUTION - Liang Y. (My University, 2000)
The effects of solid solution and solid state diffusion on crystal dissolution in a multicomponent liquid was examined by studying exact and approximate solutions to equations governing isothermal-isobaric diffusive dissolution of a crystalline solid solution in binary and ternary liquids. The dissolution rate is proportional to the square root of time in diffusive dissolution. The effect of solid state diffusion is to change the dissolved crystal composition from that in the interior of the crystal to that at the crystal-melt interface, which depends on the relative rate of diffusion in the solid to the rate of dissolution. If the dissolution rate is much faster than the diffusive exchange rate in the solid, the dissolved crystal will retain its interior or far-field composition that has not been affected by diffusion (referred to as Regime I dissolution). The dissolution rate is proportional to the diffusion rate in the liquid, independent of the crystallographic orientation of the dissolving crystal. If the dissolution rate is much slower than the rate of diffusion in the solid, the dissolved crystal will have its solidus composition at the crystal-melt interface (termed Regime II dissolution). The dissolution rate is proportional to the diffusion rate in the solid and hence dependent of the crystallographic orientation of the dissolving crystal if the degree of undersaturation is extremely small (i.e., <0.5% difference in concentrations in the liquid). Regime I dissolution is important when the diffusion rate in the liquid is more than four to six orders of magnitude faster than the diffusion rate in the solid. Convection in liquid facilitates crystal dissolution and further diminishes the role of diffusive exchange in crystal. Given the large disparities between diffusion rates in silicate crystals and diffusion rates in silicate melts (typically greater than 104), dissolution of practically all silicate xenocrysts and xenoliths in natural molten silicates are characterized by Regime I dissolution. Regime II dissolution is important when the dissolving crystal and melt are in near chemical equilibrium.